New Uzbekistan – Toward a Digital Economy (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
The article discusses the economic reforms being implemented in New Uzbekistan, the practical significance of digital technologies, the achievements being attained, and offers recommendations on the introduction of IT parks, software as a service (SaaS), platform, and infrastructure technologies.